TINJAUAN YURIDIS PERLINDUNGAN HUKUM PENGGUNA JASA TRANSPORTASI UMUM KHUSUSNYA TAKSI MENURUT UNDANG-UNDANG PERLINDUNGAN KONSUMEN - GEDE TUSAN ARDIKA; ALINE FEBRIANY LOILEWEN; TITIN TITAWATI (GANEC SWARA, 2023)
According to the Consumer Protection Act " In this thesis consists of 2 (two) sub-problems namely, (1) What is the form of responsibility of the Driver and the Lombok Transportation Company  Taxi if there is an accident on the passenger?  (2) What is the legal remedy that can be taken by passengers at the Lombok Taxi Transportation Company for accidents suffered by passengers?  To solve these sub-problems, the data collection method is used which is sourced from document studies and interviews.The results of this study indicate that: (1).  The responsibility of the taxi company towards taxi service users starts from the transport of passengers to the agreed destination.  Business operators are obliged to provide compensation for consumer losses due to accidents suffered by passengers. In carrying out its responsibilities, the Company and the driver have provided medical and maintenance costs.  (2) What legal remedies are taken by passengers at the Lombok Taxi Transportation Company for accidents suffered by passengers, carried out through court (non litigation) and through court (litigation).  Dispute resolution through out of court, carried out amicable settlement.  If the peace route is not reached, then if one party and or the parties are not satisfied, they can file a lawsuit in the district court in the general court environment.